2022
DOI: 10.3390/sports10050073
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α Methylation, miR-23a, and miR-30e Expression as Biomarkers for Exercise- and Diet-Induced Mitochondrial Biogenesis in Capillary Blood from Healthy Individuals: A Single-Arm Intervention

Abstract: Healthy mitochondria and their epigenetic control are essential to maintaining health, extending life expectancy, and improving cardiovascular performance. Strategies to maintain functional mitochondria during aging include training; cardiovascular exercise has been suggested as the best method, but strength training has also been identified as essential to health and healthy aging. We therefore investigated the effects of concurrent exercise training and dietary habits on epigenetic mechanisms involved in mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Furthermore, elite athletes, individuals who participated vigorously in competitive sports (for the past 2 years), and anyone with a history of chronic illness or medication use have been excluded from participation. The participants received a 12-week training intervention that included both endurance and strength training, as previously published by Krammer et al 2022 [ 55 ]. During their training sessions, they were supervised by the gym trainers and our staff and had to keep a training log.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, elite athletes, individuals who participated vigorously in competitive sports (for the past 2 years), and anyone with a history of chronic illness or medication use have been excluded from participation. The participants received a 12-week training intervention that included both endurance and strength training, as previously published by Krammer et al 2022 [ 55 ]. During their training sessions, they were supervised by the gym trainers and our staff and had to keep a training log.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that PGC-1α methylation decreased after the intervention, while PGC-1α methylation increased with the consumption of red and processed meat, and mtDNA content increased with the ingestion of cruciferous vegetables. These results indicate that concurrent training could improve mitochondrial biogenesis and its functions by altering the epigenetic regulation [7]. Exercise changes the mitochondrial content and quality, which is beneficial for metabolic health.…”
Section: Nutritional Factors and Inflammation In Early Lifementioning
confidence: 77%
“…Adaptation to exercise leads to a release of miRNAs from muscle tissue and other organs into our blood circulation [7,9]. This has the potential to affect signaling pathways such as the IGF1/PI3K/AKT/mTOR axis, which are changing rapidly during exercise and recovery.…”
Section: Nutritional Factors and Inflammation In Early Lifementioning
confidence: 99%
“…Since mitochondria supply energy and epigenomic substrates to the nucleus and interact with it closely via mitohormetic and mitonuclear balance systems [ 148 , 149 ] metabolic inhibition implies epigenomic disruption. Mitochondrial inhibition is well established as one of the key hallmarks of aging [ 1 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 ] and implicated pathophysiological pathways include such novel mechanisms as the leakage of mitochondrial DNA into the cytosol and stimulation of innate γ-interferon-dependent immunity via the cGAS-STING pathway [ 156 ].…”
Section: Resultsmentioning
confidence: 99%